Determinasi Pengetahuan Masyarakat tentang Produk Bank Syariah: Akses Informasi, Pendidikan, Pengalaman, dan Sosialisasi - Elex Sarmigi; Endah Sri Wahyuni; Bustami Bustami; Azhar Azhar; Samsul Bahry Harahap; Eva Sumanti (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
This study aims to analyze the influence of education, access to information, experience, and Islamic banking socialization on the level of public knowledge regarding Islamic banking products. The study employed a quantitative approach using a survey design. Data were collected through Likert-scale questionnaires distributed to 264 respondents in Sawahan Koto Majidin Village selected through a sampling technique. Data analysis was conducted using multiple linear regression, including partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The findings reveal that, partially, education, access to information, and experience do not have a significant effect on the public’s level of knowledge regarding Islamic banking products. In contrast, Islamic banking socialization has a positive and significant effect. Simultaneously, all independent variables significantly influence the level of public knowledge. These findings indicate that improving public literacy regarding Islamic banking products is more effectively achieved through intensive and sustainable socialization and educational programs. This study highlights the importance of integrated educational strategies in strengthening public Islamic financial literacy.